INCREASING THE SPIRITUAL AND INTELLECTUAL POTENTIAL OF YOUTH: KEY ISSUES IN PATRIOTIC EDUCATION (Scientific journal of the Fergana State University, 2025)
This article analyzes current issues of increasing the spiritual and intellectual potential of young people, educating them in the spirit of patriotism. The study examined the influence of the education system, information space, intellectual development and patriotic education on the consciousness of young people. Also, based on a sociological survey and empirical analysis, the attitude of young people to national values, interest in science and innovation, and the level of Internet use were studied. The article provides practical recommendations for strengthening the national identity of young people, developing innovative thinking, ensuring information security and increasing the sense of patriotism.